2020
DOI: 10.1002/bimj.202000189
|View full text |Cite
|
Sign up to set email alerts
|

An ensemble approach to short‐term forecast of COVID‐19 intensive care occupancy in Italian regions

Abstract: The availability of intensive care beds during the COVID‐19 epidemic is crucial to guarantee the best possible treatment to severely affected patients. In this work we show a simple strategy for short‐term prediction of COVID‐19 intensive care unit (ICU) beds, that has proved very effective during the Italian outbreak in February to May 2020. Our approach is based on an optimal ensemble of two simple methods: a generalized linear mixed regression model, which pools information over different areas, and an area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 28 publications
2
30
0
2
Order By: Relevance
“…Due to very limited pre-existing immunity, SARS-CoV-2 has the potential to be highly infectious. Simultaneously, pathogenicity is high enough to generate a proportion of severe cases( Buss et al, 2021 , DelSole et al, 2020 ) that can overwhelm health systems( Grasselli et al, 2020 , Farcomeni et al, 2021a ) when prevalence is high. Monitoring the epidemics is therefore a priority for policy, planning, and resource allocation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to very limited pre-existing immunity, SARS-CoV-2 has the potential to be highly infectious. Simultaneously, pathogenicity is high enough to generate a proportion of severe cases( Buss et al, 2021 , DelSole et al, 2020 ) that can overwhelm health systems( Grasselli et al, 2020 , Farcomeni et al, 2021a ) when prevalence is high. Monitoring the epidemics is therefore a priority for policy, planning, and resource allocation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate the expected values at day s + t in (6), the average of the number of patients on day s + t at both departments is taken over all simulations runs. Next, in order to estimate the boundaries in (7) for a given day s + t, the respective empirical quantiles are taken over the simulated occupancy on that day for both departments. Furthermore, in order to determine the expressions in ( 9) and ( 10), the maximum occupancy is determined for both departments from the forecast day (time s) until the end of the forecasting horizon (time s + t).…”
Section: Generation Of the Poisson Arrival Location Model And Forecasting Ward And Icu Bed Occupancymentioning
confidence: 99%
“…With data on COVID-19 patients becoming more and more available, prediction of the infection rate a few days ahead of time [10,31], and of the LoS [22] is possible. Predictions of the number of hospitalised COVID-19 patients based on regression methods are, e.g., reported in [7,8,18]. The LoS distribution of COVID-19 ICU patients in the United Kingdom is fitted to probability distributions in [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been taken with 80% of American counties; however, further work can be done to precisely include more variables in the model and specify the said angles. 20 Testing is one such variable that is often not included in models and is a major factor: Comprehensive testing as early as 31 December, 2019, in Vietnam and South Korea along with quarantine laws, flight bans and limited proximity on flights have suppressed their COVID-19 spread by providing more targeted treatment, despite raising detected cases and prevalence. Bayesian analysis utilizing total testing variability as an impacting factor on the total increases in prevalence showed that there was a decrease in infectivity in Orange County following a stay at home order.…”
Section: Modelled Projections and Considerations Of Covid-19mentioning
confidence: 99%